2020
DOI: 10.3390/cancers12123851
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to PD-1/PD-L1 Blockade in Lung Cancer: Mechanisms and Patterns of Failure

Abstract: Immunotherapy is now the preferred treatment for most lung cancer patients. It is used to treat unresectable stage III non-small-cell lung cancer and is the first-line therapy for non-oncogene-driven advanced/metastatic non-small-cell lung cancer patients (either alone or in combination with chemotherapy). Unfortunately, most patients that respond initially to immunotherapy develop resistance over time, thus limiting the durability of immunotherapy. A better understanding of the mechanisms of acquired resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…Just as the PACIFIC trial evaluated the efficacy of durvalumab consolidation therapy in patients with NSCLC after simultaneous RT and chemotherapy, the results showed that the mPFS was 16.9 vs. 5.6 months (HR: 0.55, 95% CI: 0.45-0.68), and the mOS was 47.5 vs. 28.1 months (HR: 0.55, 95% CI: 0.45-0.68) (41). In addition, a retrospective study at the 2020 ASCO conference showed that local treatment can significantly improve survival benefits (42). After immune resistance, local therapy combined with immunotherapy can reverse drug resistance to some extent, providing new treatment ideas for patients with immune drug resistance.…”
Section: Combined Radiotherapy With Immunotherapymentioning
confidence: 99%
“…Just as the PACIFIC trial evaluated the efficacy of durvalumab consolidation therapy in patients with NSCLC after simultaneous RT and chemotherapy, the results showed that the mPFS was 16.9 vs. 5.6 months (HR: 0.55, 95% CI: 0.45-0.68), and the mOS was 47.5 vs. 28.1 months (HR: 0.55, 95% CI: 0.45-0.68) (41). In addition, a retrospective study at the 2020 ASCO conference showed that local treatment can significantly improve survival benefits (42). After immune resistance, local therapy combined with immunotherapy can reverse drug resistance to some extent, providing new treatment ideas for patients with immune drug resistance.…”
Section: Combined Radiotherapy With Immunotherapymentioning
confidence: 99%
“…PD-1 and PD-L1 foster the immunosuppressive microenvironment, invalidate immunological surveillance, and help tumor cells escape from T cells via various pathways [14][15]. Different from CTLA-4, PD-1/PD-L1 pathway expresses its inhibitory function in a more indirect way.…”
Section: Function Of Pd-1/pd-l1mentioning
confidence: 99%
“…Since the recognition of antigenic peptides is necessary for effective T cell-mediated response to ICIs, the loss of antigen and MHA molecules presentation leads to acquired resistance to ICIs [14]. Scientists have identified that immunoediting can trigger the development of tumor clones with low MHC (major histocompatibility complex) expression or poor bind between neoantigens and MHC during tumorigenesis [14,21,22]. PD-1 blockade can reinvigorate exhausted CD8 + T cells (Tex), restoring their anti-tumor effector functionality [23].…”
Section: Acquired Resistance To Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations